CIVIC AWARENESS AND ENGAGEMENT IN GHANA: THE CURRICULAR IMPLICATION - Abudu, Amadu Musah; Fuseini, Moses Naiim (European Scientific Journal, ESJ, 2014)
This study examined the curricular implications of civic awareness and engagement. It specifically focused on civic activities discussed, the level of awareness of civic issues and whether a difference existed between the respondent’s general level of awareness and their civic engagement. The study employed the control group design. The sample size was 120 respondents. A structured questionnaire aided in data collection. The results showed that the respondents with citizenship education endorsed all the civic activity items depicting that they have received education on them, and that the experimental group’s level of awareness on all the civic issues was higher as compared to that of the control group. The findings again showed that there is a significant difference between people with citizenship education and those without citizenship education’s general level of awareness of civic issues. In addition, the results indicated that there is a significant difference between people with citizenship education and those without citizenship education’s wish to take part in community service. The main conclusions drawn from this study is that the difference in the level of civic awareness is due to citizenship education, and that civic awareness increases the likelihood of a person engaging in civic activities. The study recommends that the school curriculum should include activities that promote civic awareness and civic engagement.